RELIGIOUS FESTIVALS: CONVERGENT AND DIVERGENT FACTORS - Vineeth, V F (Journal of Dharma, 2003)
From the very ancient days the humans look up to heaven to fix up the dates of religious festivals. The human beings have a cosmic nature. To their cosmos belong all the planets, the earth on which they live, the space, the air, the trees and, finally, all the planets in the sky. But one planet was considered special as far as the time of religious festivals was concerned. This was the moon, the lovely daughter of heaven. The psalmist says: “Thou has made the moon to mark the seasons of festivals” (Psalm 104:19). The moon with her waning and waxing dynamics invited mankind to count time, fix up dates, months and, finally, dates for festivals. In India and Israel almost all religious festivals are fixed up based on the lunar movement.